125. Dynamic PET facilitated Pharmacokinetic Modeling and High-dose Rifampin Regimens for Staphylococcus aureus Orthopedic Implant Associated Infections: Bench to Bedside. (4th December 2021) - Gordon, Oren; Lee, Donald; Langevin, Brooke; Ordonez, Alvaro A; Dikeman, Dustin; Shafiq, Babar; Thompson, John; Flavahan, Kelly; Lodge, Martin; Rowe, Steven; Dannals, Robert; Ruiz-Bedoya, Camilo; et al.
Abstract: Background: Rifampin, has potent, dose-dependent sterilizing activity against Gram-positive bacteria with the area under the concentration-time curve (AUC) being the most predictive of bactericidal activity. Combination therapy with rifampin (10-15 mg/kg/day) is recommended to treat S. aureus orthopedic implant associated infections. Recently, high-dose rifampin (35 mg/kg/day) has been shown to be safe in humans and is being evaluated to shorten tuberculosis treatments. Methods: Dynamic 11 C-rifampin (chemically identical to rifampin) positron emission tomography (PET) was used to determine rifampin bone exposures (AUC) in mice and patients with S. aureus bone infection (Figure 1 ). PET data facilitated a pharmacokinetic model to predict rifampin concentration-time profiles in bone tissues, which were used to design studies in a mouse model of S. aureus orthopedic implant infection utilizing advanced imaging. Figure 1. Experimental schematics. (A) A validated mouse model of S. aureus orthopedic implant associated infection was used to determine bone concentrations following administration of escalating rifampin oral dosing (human equipotent dosing is indicated). m/z, mass/charge ratio. (B) Human patients and mice with S. aureus orthopedic infection were imaged using 11C-rifampin PET / CT. PET signal was quantified in infected and uninfected bone to generate time-activity curves (TACs) used to calculate area under the concentration time curve (AUC) over 45-90 minutes. These data were used to develop a pharmacokinetic model to predict rifampin exposures in bone. (C) Efficacy studies in mice compared vancomycin alone to vancomycin with either standard-dose or high-dose rifampin. Readouts included weekly in vivo bioluminescence, bacterial load and broth cultures at completion of follow up and CT to evaluate adverse bone remodeling. Bacterial isolates were evaluated for phenotypic resistance as well as subjected to whole genome sequencing. Human studies were approved by the Johns Hopkins University Institutional Review Board Committee. Patients were prospectively recruited at the Johns Hopkins Hospital and 11C-rifampin PET was performed under the U.S. FDA Radioactive Drug Research Committee program guidelines for investigational drugs. Animal studies were approved by the Johns Hopkins Animal Care and Use Committee. Approvals from the Johns Hopkins Biosafety, and Radiation Safety were also obtained for all studies. Results: 11 C-Rifampin PET median bone to plasma AUC ratio was 0.14 (IQR 0.09 – 0.19) in patients (Figure 2A-E ), lower than previously reported using single time-point measures. Pharmacokinetic simulations and tissue measurements demonstrated that administration of high-dose rifampin leads to substantial increases in bone tissue concentrations (Figure 2F-G ). Importantly, 4-weeks of high-dose rifampin administered in combination with vancomycin was non-inferior to the 6-weeks combination treatment with standard dose rifampin and vancomycin, recommended by the IDSA [risk difference: -6.7% (-20% – 6.9%) favoring high-dose rifampin] (Figure 3 ). Finally, high dose rifampin ameliorated antimicrobial resistance (0% vs 40%; P = 0.04), genetic alterations related to persistence (whole-genome bacterial sequencing) (Figure 4A-B ) and mitigated adverse bone remodeling (high-resolution computed tomography) (Figure 4C-D ). Figure 2. Rifampin bone exposures. (A) Three patients with S. aureus bone infections underwent dynamic 11C-rifampin PET for 60-90 minutes, followed by a CT scan. Frontal view of maximum intensity projection (PET) is shown. Note an implant in the left tibia (arrow). (B) 11C-Rifampin PET area under the concentration-time curve (AUC) shown as a heat map overlay in the selected transverse section. (C) Representative human time-activity curve (TAC). (D) 11C-rifampin exposure in human is shown as AUC ratio of bone to plasma, corrected for hematocrit and tissue density. Whenever possible infected bone was compared to uninfected contralateral bone. Plasma exposures were measured by drawing volumes of interest (VOI) in the left ventricle. (E) Dynamic 11C-rifampin PET in control patients (with pulmonary TB; from an unrelated study) (n = 12 patients). VOIs were drawn in uninfected bone as indicated. Mice were instrumented with a femoral Kirshner wire and infected with Methicillin-resistant S. aureus (SAP231) and followed for 2 weeks before antibiotic treatment was initiated with vancomycin and rifampin (BID dosing), corresponding to a human equipotent rifampin dose of 10, 35 and 45 mg/kg/day. Rifampin plasma (F) and bone (G) concentrations were measured by mass spectrometry in postmortem samples at 4 hours after last rifampin oral dose. (H) Mice underwent dynamic 11C-rifampin PET for 60 minutes following at least two weeks of antibiotic treatment, followed by a CT scan (n = 8 animals). Frontal view of maximum intensity projection (PET) is shown. Note the implant in the right knee (arrow). (I) Representative mouse TAC showing rapid decrease in plasma levels and accumulation in the liver. (J) 11C-Rifampin exposure in mouse shown as AUC ratio of bone to plasma (corrected for hematocrit) and tissue density using the mean Hounsfield units per VOI. VOIs were drawn for the infected femur (distal 25%) and the uninfected contralateral femur. Plasma exposures were measured by drawing VOI in the left ventricle. *p<0.05, †p<0.01 and ‡p < 0.001 as shown by the Kruskal-Wallis test (panels E, F and G) or by the Wilcoxon matched-pairs signed rank test (panel D), both adjusted for multiple comparisons to preserve the desired false discovery rate or by the 2-tailed Mann-Whitney test for comparison of infected to uninfected bone (panels G and J). Figure 3. Non-inferiority study in mice with S. aureus-implant infection. (A) Vancomycin and rifampin were initiated 2 weeks after infection (designated as day 0) and continued for 6 weeks (IDSA regimen, standard dose rifampin; n = 45 animals) or for 4 weeks (high-dose rifampin; n = 45 animals). Standard- and high-dose rifampin doses were (human equipotent) 10 and 35 mg/kg/day respectively. Monotherapy with vancomycin over 6 weeks was also performed (n = 10 animals). Stable cure was assessed at day 84 by assessing sterilization of the tissues and the implant. (B) Representative in vivo bioluminescent images from mice in each group. (C) Mean maximum flux (photons/s/cm2/sr) (and SEM). LOD = level of detection (3x103 photons/s/cm2/sr). (D) Six weeks after completion of antibiotic treatment, peri-implant joint and bone tissue were homogenized, implants were sonicated, and colony forming unit (CFUs) were enumerated ex vivo. Data are presented as the mean number of CFUs (and SEM) isolated from the peri-implant bone and joint tissue. (E) To evaluate whether the antibiotic therapy eradicated infection, tissue homogenates and implants were cultured for an additional 48 hours in broth followed by overnight plate culture and the presence or absence of bacterial growth was determined. Data are presented as the percentage of tissue samples with any bacterial growth. (F) Statistical analysis showing treatment difference in favor of high-dose rifampin and 90% confidence interval within the pre-set limit for non-inferiority (d=10%). *p<0.05, †p<0.01 and ‡p < 0.001 as shown by the Kruskal-Wallis test adjusted for multiple comparisons to preserve the desired false discovery rate. Figure 4. Bacterial characteristics and bone remodeling. All isolates from the non-inferiority study (Fig. 3; n = 21 isolates) were subjected to (A) phenotypic rifampin resistance testing (BD Phoenix) with results presented as the percentage of resistant isolates for each treatment group and (B) whole genome sequencing (Illumina; MiGS, Pittsburg, PA) and compared to the parent strain SAP231. Heat maps display isolates with variants in genes related to rifampin resistance (rpoB) or to bacterial persistence (lysM, sdhB and clfB). (C) Representative 3D reconstructed µCT images (opaque [top] and translucent [bottom] femora with implants in red). (D) Mean (and SEM) volume of the distal 25% of the infected femurs. *p<0.05, †p<0.01 and ‡p < 0.001 as shown by the Chi-square test (A) or by the Kruskal-Wallis test adjusted for multiple comparisons to preserve the desired false discovery rate (D). Conclusion: Standard dose rifampin achieves sub-therapeutic levels in bone which can be substantially increased with higher doses. High dose rifampin ameliorates antimicrobial resistance and mitigate bone remodeling, facilitating shorter treatment in mice. Clinical studies are needed to examine the safety and efficacy of high dose rifampin for staphylococcal bone infections in humans. Disclosures: Alvaro A. Ordonez, MD, Cubresa (Consultant)Fujirebio Diagnostics (Research Grant or Support) Robert Dannals, PhD, Precision Molecular Imaging (Consultant) Nathan Archer, PhD, Boehringer Ingleheim (Grant/Research Support)Integrated Biotherapeutics (Grant/Research Support)Pfizer (Grant/Research Support) Lloyd Miller, MD PhD, Armirall (Consultant)AstraZeneca (Consultant, Grant/Research Support)Boehringer Ingelheim (Grant/Research Support)Integrated Biotherapeutics (Board Member, Consultant)Janssen Research & Development, the pharmaceutical company of Johnson & Johnson (Consultant, Employee, Shareholder)Moderna Therapeutics (Grant/Research Support)Noveome Biotherapeutics (Shareholder)Pfizer (Grant/Research Support)Regeneron Pharmaceuticals (Grant/Research Support) Sanjay K. Jain, MD, Fujirebio Diagnostics, Inc., USA (Research Grant or Support)Novobiotic LLC, USA (Research Grant or Support)T3 Pharma, Switzerland (Research Grant or Support) Sanjay K. Jain, MD, Fujirebio Diagnostics, Inc., USA (Individual(s) Involved: Self): Research Grant or Support; Novobiotic LLC, USA (Individual(s) Involved: Self): Research Grant or Support; T3 Pharma, Switzerland (Individual(s) Involved: Self): Research Grant or Support